Evolutionary conservation and enhanced basal immunity of the ZmNBS gene family in maize - Xu, Zhe; Feng, Liying (Frontiers in Plant Science, 2025)
The nucleotide-binding site (NBS) gene family is central to plant innate immunity. However, a comprehensive understanding of its evolutionary dynamics and functional diversity in maize, particularly within a pan-genomic context, remains limited. We conducted a systematic pan-genomic analysis of the ZmNBS gene family across 26 representative maize inbred lines. Our approach integrated evolutionary genetics, structural variation analysis, and expression profiling to investigate presence-absence variation (PAV), duplication modes, evolutionary rates, and the impact of structural variants (SVs). We observed extensive presence–absence variation (PAV), distinguishing conserved “core” subgroups (ZmNBS31 and ZmNBS17-19) from highly variable ones (ZmNBS1-10 and ZmNBS43-60), thereby supporting a “core-adaptive” model of resistance gene evolution. Duplication mode analysis revealed subtype-specific preferences: canonical CNL/CN genes largely originated from dispersed duplications, while N-type genes were enriched in tandem duplications. Evolutionary rate analysis showed that whole-genome duplication (WGD)-derived genes exhibited strong purifying selection (low Ka/Ks), whereas tandem and proximal duplications (TD/PD) showed signs of relaxed or positive selection. Structural variants (SVs) were associated with altered motif structures and significantly impacted gene expression. Notably, ZmNBS31 emerged as a conserved, highly expressed gene under both stressed and control conditions, underscoring its potential role in basal immunity. Our findings demonstrate how duplication mechanisms, structural variations and differential selection pressures collectively shape the evolution of the ZmNBS gene family. The identification of ZmNBS31 as a candidate for basal immunity, along with our established "core-adaptive" framework, provides valuable insights and a conceptual foundation for identifying and improving broad-spectrum resistance genes in maize breeding programs.